Encashing remunerative returns from integrated farming system model through farmer participatory approach - Burman, R Roy; Sahu, Subhashree; Sharma, Shailendra; Singh, Rahul; Padaria, R N; Rohilla, P P; Singh, S K; Singh, A K (Indian Farming, 2022)
Integrated Farming System (IFS) model helps in efficient utilization of farm resources and risk minimization for farmers. The incorporation of such diversification in the conventional rice-wheat cropping system has led to enhanced returns by 43–98%. Theintegration of enterprises like mushroom unit has helped in the recycling of farm wastes and thus helped in generating wealth from waste. The component of fish production is very much profitable and contributes a major share of the total farm income after the cereals and pulse component and thus, needs to be upscaled and promoted effectively. The vegetables cultivation hashelp ensure nutritional security for the family and also generate handsome returns from the market. Similar is the case with the flower component of the model, which fulfills the household needs along with catering to the urban market and getting handsome returns out of it. Fodder cultivation has improved the soil fertility status and water holding capacity of the soil. The abovediscussedmodel can be an inspiration and eye-opener for young enterprising farmers to follow the market trend and invest in the diversified allied enterprises for generating higher returns.